THE FAILURE OF MECCA AGREEMENT IN DEESCALATING THE CONFLICT BETWEEN HAMAS AND FATAH - Habibi Kurniawan (IPIREL UMY, 2009)
ABSTRACT ABSTRACT This undergraduate thesis aims to explain the failure of Mecca Agreement for deescalating the civil armed conflict between Hamas and Fatah in Palestine. As the resulted, mass casualties were conducted rapidly between both parties, therefore it is important to evaluate the role of Mecca Agreement and post-Mecca Agreement negotiation as the final peace agreement in maintaining the conflict resolution for the shake of betterment in Palestine. To give the comprehensive understanding in